1993
DOI: 10.1042/bj2900515
|View full text |Cite
|
Sign up to set email alerts
|

The xylan-degrading enzyme system of Talaromyces emersonii: novel enzymes with activity against aryl β-d-xylosides and unsubstituted xylans

Abstract: Talaromyces emersonii, a thermophilic aerobic fungus, produces a complete xylan-degrading enzyme system when grown on appropriate substrates. In this paper we present the physicochemical and catalytic properties of three enzymes, xylosidase (Xyl) I (M(r) 181,000; pI 8.9), II (M(r) 131,000; pI 5.3) and III (M(r) 54,200; pI 4.2). Xyl I and II appear to be dimeric and Xyl III is a single-subunit protein. All three enzymes catalyse the hydrolysis of aryl beta-D-xylosides and xylo-oligosaccharides. Xyl I is a class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…3). Through other studies conducted in this laboratory [20,22,23], T. emersonii is known to produce an array of extracellular carbohydrate-modifying enzymes that can depolymerize pectin polysaccharides. Production of these enzymes during growth on citrus pectin may provide a continuous supply of readily metabolized sugars, which may explain the consistent expression of the m-MDH gene throughout the specified growth period.…”
Section: Northern Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…3). Through other studies conducted in this laboratory [20,22,23], T. emersonii is known to produce an array of extracellular carbohydrate-modifying enzymes that can depolymerize pectin polysaccharides. Production of these enzymes during growth on citrus pectin may provide a continuous supply of readily metabolized sugars, which may explain the consistent expression of the m-MDH gene throughout the specified growth period.…”
Section: Northern Analysismentioning
confidence: 99%
“…T. emersonii is distinguished from thermotolerant counterparts by its growth temperature range of 30-65°C and ability to thrive at growth temperatures between 45 and 55°C (data from our laboratory and [17]). Work conducted in our laboratory has revealed that T. emersonii produces a potent array of complete, multicomponent enzyme systems that degrade key biopolymers in nature, including proteins and various terrestrial and marine plant carbohydrates [18][19][20][21][22][23][24]. In addition, more recent studies have revealed that T. emersonii may be a Pandora's box of other interesting glycosyl hydrolases and oxidoreductases, many of which have homologs in model eukaryotic species [25,26].…”
mentioning
confidence: 99%
“…Groups of enzymes are arranged into 'systems', such as xylan-degrading (Tuohy et al, 1993;Myburgh e t al., 1991 ; Johnson e t a/., 1988) and cellulose-degrading (Beguin e t al., 1992;Wood, 1992). The nature of these enzyme-substrat:e interactions and cooperativity between enzymes are presently the subject of extensive research, especially concerning the breakdown of cellulose and hemicellulose , because of possible exploitation in agricultural and industrial processes .…”
Section: Introductionmentioning
confidence: 99%
“…It has generally recognized as safe (GRAS) status, making it a biotechnologically relevant organism to rival Aspergillus and Trichoderma species for the production of important industrial enzymes. T. emersonii has been shown to secrete a wide array of hydrolytic enzymes under defined growth conditions, and possesses complete xylan-and cellulasedegrading systems that consist of diversified carbohydrases (Heneghan et al, 2007;Murray et al, 2001Murray et al, , 2003Reen et al, 2003;Tuohy et al, 1993Tuohy et al, , 1994Tuohy et al, , 2002. Previously, we have shown that the presence of peptides in growth media induces expression of an extracellular peptidase with broad substrate specificity in T. emersonii (O'Donoghue et al, 2008).…”
Section: Introductionmentioning
confidence: 99%